Inducing to the rooting of teak (Tectona grandis l.f.) - Georgin, Jordana; Bazzoti, Ronaldo; Perrando, Edson (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The objective of this study was to evaluate the response in front the induction of rooting of the Tectona grandis L. f (Teca) with the assis- tance of the induction rooting hormone IBA (Indolbutyric Acid). The study was developed at the forest nursery UFSM/CESNORS campus situated in the city of Frederico Westphalen – RS. As from eight plants were obtained cuttings of caulinar and nodal segments. It promoted two treatments: control without the use of IBA and IBA 2000 ppm, ocurring at the immersion of base of the cuttings for 10 seconds, with each plant corresponded to one repetition. The experiment was evaluated biweekly how much the survival and sprouts formation, and two other opportunities in relation to the rooting and callus formation at the base of the cuttings. There was not success how much on the rooting, occurring only to callus formation and emission of sprouts on cuttings related to nodal segments containing presence of axial gems. It was observed that genetic variability might have affected strongly on survival time and pre-disposition to the plant cell dedifferentiation.